Microelectronics, Nanoelectronics: step behind the red brick wall using the thermal domain. (2019) - Mizsei, J.; Lappalainen, J.
Abstract: The More-than-Moore Grand Challenge is a hot topic of present day solid state electronics: one way to step behind the "red brick wall" is the 3D heterogeneous integration of different systems with the conventional (standard) CMOS-technology. The aim of this study is to summarize the different bit representation methods, especially possibilities of our new, patented phonsistor (phonon transistor) based thermal-electronic logic system or thermal-electronic logic circuit (TELC). TELC is the first logic gate approach using two different physical quantities, i.e. electrical and thermal for bit representation within one system